UNCOMMON WORDS USED IN MARKET PLACE: A SEMANTIC ANALYSIS OF LIVE ONLINE SHOPPING UTTERANCES - Wahyu Trimastuti; Santy Christinawati (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2023)
The aim of the research is to analyze the process of word formation from uncommon words of online shopping in the markets place used by Gen Z. Specifically, the purpose of this research is to identify how the process of forming the uncommon terms often used in live online shopping, identify the kind of word formation in those terms, and explain the meaning of the terms. Researchers used two theories to conduct this research; namely the theory by Yule and Petada. In this study, the researcher used a qualitative descriptive method. The data was collected from a live online shopping in market place in January 2023. The writer used document and observation method to collect the data. The writer analysed the words based on the elements of words. The results of this study indicated that only three word formation processes made up the eleven data found in the data source: compounding, affixation, and acronyms; acronym was the process that forms the most terms in the report as many as six terms, the second was compounding with three terms, third was affixation with two terms. Those terms had complexity in the process of its formation and had specific meaning. Therefore, it is necessary to be explained more detailed to avoid misunderstanding in communication.